Decrease in the Frequency of Circulating CD56+CD161+ NK Cells in Human Visceral Leishmaniasis. (17th February 2018) - Rai, Ambak Kumar; Thakur, Chandreshwar Prasad; Kumar, Prabin; Saini, Sheetal; Kureel, Amit Kumar; Kumari, Smita; Seth, Tulika; Mitra, Dipendra Kumar
ABSTRACT: Background: Natural Killer (NK) cell plays an important role in the innate immune system and is known to produce IFN-γ at an early stage of infection that is essential to eliminate intracellular infection like Leishmania spp. It is already established that Leishmania parasite inhibits the activity of NK cells, avoiding the encounter with the early innate immune response. This, in turn, favors establishment and further dissemination of the infection. Methods: In the present study, we have tried to measure the frequency of different phenotypic subsets of NK cells among visceral leishmaniasis (VL) patients. Results: We have phenotyped three distinct three distinct subsets (CD56 – CD161 +, CD56 + CD161 –, and CD56 + CD161 + ) of NK (CD3 – ) cell using their specific markers CD161 and CD56. Conclusion: Interestingly, we observed selective loss of CD56 + CD161 + subset of circulating NK (CD3 – ) cells. Importantly, the other subsets (i.e., CD56 − CD161 + and CD56 + CD161 – ) of circulating NK cells remain unaffected as compared with healthy subjects.